GF120 effects on fruit fly species (Diptera Tephritidae) in Sahelian agroforestrybased horticultural cropping systems - Zakari-Moussa, O.; Ratnadass, A.; Vayssières, Jean-François; Nikiema, A.; Fatondji, D.; Salha, H.; Aboubacar, K.; Ryckewaert, P.; Pasternak, D. (EDP Sciences, 2012)
Introduction. In the water-saving and income-generating agroforestry cropping systems developed and promoted by the ICRISAT in the Sudano-Sahelian zone of West Africa, particularly in Niger, fruits of domesticated Ziziphus mauritiana (“apples of the Sahel”) are severely damaged by fruit flies (Carpomya incompleta), and chemical pesticide application poses economic, environmental and human health problems. In the Bio-reclamation of Degraded Lands (BDL) system, apple of the Sahel is the main high-value crop, while in the Dryland Eco-Farm (DEF), it is grown alongside watermelon. Sclerocarya birrea (marula plum) is presently being investigated as a dryland tree species for fruit and oil production, either in orchards or such systems as BDL. Materials and methods. To complete preliminary results of earlier studies published elsewhere, we collected and incubated in 2010 ripe fruits of marula plum and watermelon in Sadoré, Niger, where the above-mentioned agroforestry systems are developed, and we recorded emerging fruit flies. We also conducted a spot-spraying experiment (using GF-120) in an apple of the Sahel orchard in Niamey in 2010; we recorded undamaged and damaged fruits and incubated the latter. In the same orchard, we set up in 2011 a fruit fly trapping survey targeting the invasive species Bactrocera invadens (Chempac® traps using methyl eugenol as the attractant). Results and discussion. The results showed that only Ceratitis cosyra emerged from marula plums, and only Dacus spp. from watermelon. The GF-120 spot-spraying experiment showed that C. incompleta was not attracted / intoxicated, contrary to Ceratitis spp. and Dacus spp.; the sprayed trees yielded significantly more marketable fruits than unsprayed ones; only C. incompleta emerged from damaged fruit. Detection trapping revealed for the first time the presence of B. invadens in the Sahelian zone of Niger, including at the time of apple of the Sahel fruit production. Conclusion. This, alongside results of earlier studies, suggests a repellent effect of GF-120 on the monophagous C. incompleta species (Trypetinae), while it is attractive to oligophagous/polyphagous Dacinae fruit flies; some of them (e.g., Dacus spp.) damage watermelon, which is part of the DEF system, and produce fruit at the same time as the jujube tree. The prospects for harnessing these two opposite regulation pathways are discussed.